Efek Mediasi Kepuasan Pelanggan pada Hubungan Kualitas Layanan dan Produk dengan Loyalitas Pelanggan Restoran - Remiasa, Marcus; Hutoyo, Agam Pilar Bajik; Aprilia, Lola (Syntax Corporation, 2026)
The purpose of the study was to obtain empirical evidence of the indirect influence of customer satisfaction in the relationship between service quality and product quality and restaurant customer loyalty. The research sample consisted of 160 respondents who were visitors to Hachi-Hachi Bistro Surabaya. Sample extraction is carried out using a non-probability sampling technique with a purposive sampling type where each customer does not have the same probability to become a research sample. The distribution of questionnaires is carried out in 2 ways, namely offline (face-to-face) and online (using google forms). The research hypothesis was tested using a structural equation model (SEM) with AMOS version 23. The results of this study provide empirical evidence that customer satisfaction mediates the relationship between service quality and product quality with customer loyalty. This study also proves that service quality and product quality have a significant positive effect on customer satisfaction, and subsequently customer satisfaction has a significant positive effect on customer loyalty.